Copper-catalyzed diastereoselective hydrothioetherification of oxa(aza)benzonorbornadienes. Issue 18 (29th April 2020) - Lin, Qifu; Yao, Yongqi; Yang, Wen; Tan, Yun; Chen, Shuqi; Chen, Donghan; Yang, Dingqiao
Abstract : A novel copper-catalyzed multicomponent one-pot syn -selective hydrothioetherification of oxa(aza)bicyclic alkenes to synthesize unsymmetrical thioethers has been established. Abstract : A novel copper-catalyzed hydrothioetherification of oxa(aza)bicyclic alkenes with potassium thioacetate and aryl or alkyl iodides to synthesize unsymmetrical thioethers has been developed. Notably, the reaction with complete diastereoselectivity went through a syn -selective addition process to give exo -adducts. In addition, this protocol exhibited high efficiency and good functional group tolerance to afford the target thioethers in moderate to good yields. Based on the results of mechanistic investigations, a plausible mechanism was proposed.